The relationship of philosphy and sociology in the light of Maurice Merleau-Ponty’s phenomenological philosophy - Eric, Milomir (Sociološki pregled, 2023)
In this paper, in the context of Maurice Merleau-Ponty’s phenomenological philosophy, the author deals with the following questions: why two disciplines, sharing the same problems, philosophy and sociology, have become distant to a large extent, and even opposed to each other. Is it possible to establish a fruitful dialogue between sociology, which was dominantly positivist at Merleau-Ponty’s time, and phenomenological and existentialist philosophy? Can the change in the manner of placing the problems about society help to bridge the abyss between “absolutely self-sufficient” philosophy and sociology that, unaware of its theoretical suppositions, “only collects facts”? Can fundamental sociological concepts – social fact, role, culture, institutions etc. – be redefined so that they become the subject of philosophical analyses and at the same time revitalize philosophical layers of sociology itself? One of possible solutions to overcome such unnatural separation of these two disciplines is to raise awareness about and emphasize their common foundations, because a philosopher also thinks about scientific facts, just as a sociologist, every time when reconsidering the conceptual network in an attempt to include social facts, when returning to live sources of his knowledge – actually philosophizes. Apart from the analysis of the relationship of sociology and philosophy, the manner is emphasized in which positivist and phenomenological methods perceive and understand their mutual relationship.